A comparison of underground coal mine emergency management in China and Australia. (2017) - Xi, Jian; Cliff, David; Wu, Zongzhi
This paper introduces current practices on underground coal mine emergency management in China and Australia. From aspects of prevention, preparedness, response and recovery (PPRR), methods, measures and technology applied in two countries on underground coal mine emergency management are compared. The influences of education, engineering and enforcement (3E) on accident prevention in both countries are analysed. Differences on legislations, emergency plans, organisation, equipment and exercises during emergency preparedness are enumerated as well as the reasons leading to these differences. On the aspect of emergency response, the incident classification, command structure, evacuation and aided rescue are compared. For emergency recovery, differences on incident report rules are emphatically compared. At last, advantages and challenges of China and Australia on underground coal mine emergency management are concluded. Third party emergency services, trigger action response plans (TARPs) and high potential incidents (HPIs) are three major advantages from which China could benefit.